PERAMALAN PENERIMAAN MAHASISWA BARU DENGAN PERBANDINGAN METODE REGRESI LINIER SEDERHANA DAN SINGLE EKSPONENTIAL SMOOTHING: STUDI KASUS FTI UNIVERSITAS MERDEKA MALANG - Fauzy, Iqbal; Pramaditya, Himawan (Fakultas Sains dan Teknologi, 2024)
This forecast is specifically to provide information on the number of new students in 2024-2025 for the number of new students in 2024-2025 using data on the number of students from the last 10 years. By using error analysis, the results of which are simple linear regression methods which can be said to be successful in covering the shortcomings of single exponential smoothing.